APPLICATION OF THE PRINCIPLE OF COMMON BUT DIFFERENTIATED RESPONSIBILITIES IN FULFILLING STATE OBLIGATIONS FOR CLIMATE CHANGE UNDER THE PARIS AGREEMENT ON THE UNITED NATIONS FRAMEWORK CONVENTION ON CLIMATE CHANGE - Ida Ayu Dampaty Anja Anjani; Zunnuraeni; Guna Nugraha, Lalu (Department of Law, Faculty of Law, University of Mataram, 2024)
Climate change is now an international issue as it affects nations around the world. The Paris Agreement 2015 was established as a form of countries' efforts to reduce climate change. This research aims to find out the application of the principle of common but differentiated responsibilities in the Paris Agreement and its implementation in Indonesian law as a developing country. The research method used is the normative research method with statutory and conceptual approaches. The research results determined that the application of the principle of common but differentiated responsibilities in the Paris Agreement is based on a bottom-up approach. The approach gives the authority to determine targets for each country through the formation of nationally determined contributions containing action plans that will be implemented by a country within the next five years to realize the goals of the Paris Agreement. In its implementation in Indonesian national law, the principle of common but differentiated responsibilities is applied through the NDC which is then realized in several regulations governing capacity building, economic growth, and adaptation and mitigation.